Developing Indoor Air Quality Monitoring System Using Internet of Things and Wireless Sensor Network - Marti Widya Sari; Banu Santoso (Universitas PGRI Semarang, 2021)
Since Indoor air quality heavily affects human health, the problem of indoor air quality needs serious attention, especially when the air quality is unfriendly and containing smoke. Therefore, it requires monitoring system to determine the smoke level in a room. This study aims to develop an indoor air monitoring system based on IoT and WSN to ease the users for monitoring the air quality in the surrounding environment. The research methods employed through library research, surveys and field observations, development system and testing system. The application development stage includes analysis, system design, implementation, and testing. The air quality level monitoring application was built with the web based programming language, MySQL database, and Arduino. The level of air pollution was measured by an MQ-2 sensor that serves to detect smoke levels and a web-based application to display information. The indoor air quality monitoring system is able to display the data result through website which can be accessed via the internet. Therefore, users can access the data from the smoke-level measurement of monitored surrounding environment. The testing of the system shows that this application is feasible and applicable to be used as a device to monitor indoor air quality levels.